Uji Kualitatif dan Kuantitatif Kandungan Nitrit pada Produk Makanan Kemasan Olahan Daging yang Beredar di Super Market Kota Jambi - Zahra, Fitrah Annisa; Elisma, Elisma; Rifqi, M (Jurusan Farmasi, Poltekkes Kemenkes Palembang, 2023)
Sodium nitrite is one of the permitted food preservatives that are widely used in meat. This study aims to identify and determine the level of sodium nitrite with samples used in the form of corned beef sausage and nuggets. Identification of sodium nitrite cadarn was done by UV-Vis Spectrophotometry method. The results showed that of the 9 samples tested, all were positive for sodium nitrite. From all samples, it was found that all food samples met the standards set by the Regulation of the Head of the Food and Drug Administration Number 36 of 2013, the maximum use limit of sodium nitrite preservative in processed meat products is 30 mg/kg.